Medium-Scale Fire Resistance Testing of Timber Structures with Composite Cement Fibre Materials - Tomáš Žajdlík; Karel Šuhajda; David Průša (Buildings, 2023)
The combustibility of natural wood presents a negative impact for using this material in buildings. Timber elements can be cladded with boards made of non-combustible materials. This study represents a group of options for increasing the resistance of timber against the effects of fire and the possibility of slowing down the effect of thermal degradation of wood. The aim of this study is focused on an experimental testing of structures with timber elements protected by cement fibre boards as a non-combustible fire retardant. Cement fibre boards are fibre-reinforced composite materials used for systems of dry constructions. These boards present the highest degree of fire reaction class (A1). The behaviour of the structure, loaded by the effects of fire, was monitored during the experiment. The specimen was tested with reduced dimensions. The temperature loading corresponded to the procedure according to the standards. The final fire resistant (FR) results were evaluated in accordance with the requirements for the selected limit states of FR. This was assessed based on the measured temperatures and the whole condition of the tested specimen. The specimen fulfilled the fire-separating function of the structure for the classification times.